The sum of first q terms of an AP is 63q-3q^(2). if its p^(th) term is -60, find the value of p. also find the 11^(th) term of this AP.

Asked by Rohit Misra | 23rd Dec, 2013, 03:49: PM

Expert Answer:

Given Sq = 63q-3q2

S1 = 63 * 1 - 3* 1*1

=60 = a1

S2 = 63 * 2 - 3* 2 *2

=114

S2 - S1 = 114 - 60

=54 = a2

So, d = 54 - 60 = - 6

Now,

ap = - 60 (Given)

a + (p-1) d = - 60

60 + (p-1) (-6)= - 60

p-1 = -60-60 / -6 = 20

p = 21

Now,

a11 = a+ 10 d

=60 + 10 (-6)

= 60 + -60

= 0

Answered by  | 23rd Dec, 2013, 06:09: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.